Avaliação da aplicação da gestão interorganizacional de custos no ambiente de consórcio modular: competitividade por meio da estratégia de colaboração e redução dos custos globais das operações - Braga, Alexandre Xavier Vieira (Universidade do Vale do Rio dos Sinos, 2015)
Although there are theoretical and empirical research on modular consortium, studies on the relationship between modulists, the flow of information and the Interorganizational Cost Management (IOCM) in modular consortium arrangements are embryonic. The modular consortium and IOCM induce companies to overcome organizational boundaries in order to allow the entire value chain becomes more efficient. This thesis, configured how a Case Study with Embedded Objects, defends the possibility of accepting that the association between modular consortium and IOCM promotes mutual learning and further reducing overall operating costs in the automotive value chain, rather than taken alone. It is understood that the approaches adopted by the modular consortium in Resende (modularization and IOCM) are complementary and include several common factors, such as the sharing of R&D projects, meshing of its employees in other companies, integrated information systems, knowledge transfer as well as the need to develop a more efficient inter management. In this context, modular consortium is on a facilitator of the IOCM process because the allowable cost of the components is defined by inter-working teams, which include product design, engineering, procurement and production engineering. Thus, companies have shown a high interdependent relationship. But it is evident that not always, the benefits are shared between all the actors involved, due to the asymmetry of power between MAN and modulists. Regarding the exchange of the findings indicate a strong occurrence cost information of this initiative, but only the modulists for MAN. The empirical evidence obtained in this study denote the use of power by MAN to its modulists. The use of power may favor disclosure by modulists cost data, but this does not guarantee the success of IOCM in all its fullness. This is a limitation to the applicability of IOCM through open book accounting.
Keywords: Relações interorganizacionais; Inovação; Consórcio modular; Gestão interorganizacional de custos; Open book accounting; Inter-organizational relationships; Innovation; Modular consortia; Inter-organizational cost management; ACCNPQ::Ciências Sociais Aplicadas::Administração